Undesirable jurisprudential acts (Almukrohat alfiqhia) in the Hanbali School from book of " Sharh muntaha al- iradat, for Bahooti" from the beginning of sand ablution (Altaymmom) Chapter to end of prayer(Alsalat) Description Chapter - AL- Malki, Amal Ahmad (Journal of Humanities & Social Sciences, 2019)
This study aimed to extract the undesirable jurisprudential acts (almukrohat alfiqhia) in the Hanbali School from book of " Sharh muntaha al- iradat, for Bahooti" from the beginning of sand ablution (Altaymmom) Chapter to end of prayer(Alsalat) Description Chapter. The research organized after the introduction, in which it mentioned the importance of the subject , the reasons for its selection, the previous studies, the research methodology which that adopted extrapolation, tracking and devising.The most important aspects of the research: Linking between the science of fundamentals of jurisprudence and jurisprudence through defining the Undesirable acts at the scholars of fundamentals of jurisprudence , applying that through viewing the branches of scholars and extract the jurisprudential undesirable acts and knowing its legal proves and how the scholars in- ference by it .Through this research we can see the ease of Islam by:Sand ablution (Altaymmom) provisions , removing the Judgmental impurity (Najasa Hakamia), Menstruation . Then I shifted to prayer provisions , starting from the call to pray (Azan) Conditions of prayer , covering Awra , removing the impurity , intention to pray and finished with pray description .
Keywords: Fiqh abominations; the Hanbali school of thought; Al-Bahuti; Explanation of the ultimate wills; Chapter on Tayammum